Rain-water PLC based detector and valve switcher - Mohammad Hadi, Ismail (2008)
The main purpose of this project is to collect clean rain water automatically by using water sensor; solenoid valves, buzzer and water pump that controlled by Programmable Logic Controller (PLC). Below is modeling of the project. When rain fall, sensor 1 will be detect water and make cause valve 1 will be open for 10 second. This is because; we need to flow out the dirty water from the roof firstly. After 10 second, the valve will be close and make cause the rain water will go to the tank A. If sensor 3 detect no water, water from tank A will be pump to the tank B, with condition, sensor 2 must be detect water in tank A firstly. Finally we can use rain water from Tank B for useful purpose like flushing toilets, washing machines, watering gardens, washing cars and etc.